Structural Design Tuak River Pedestrian Suspension Bridge Anchor Block Type Rigid Symmetric with LISA - Aco Wahyudi Efendi (Elektriese: Jurnal Sains dan Teknologi Elektro, 2022)
Anchor blocks are one of the components and elements that are very risky for suspension bridge construction, because almost The ability The Suspension bridge resistance rests on the cables held in place by the anchor block. This anchor block behavior study is to find out the major stress information occurring in the anchor block elements. In this research, the researcher refers to the Circular Letter of Design Criteria for Rigid Symmetrical Pedestrian Suspension Bridge, and conducts structural modeling using the finite element method-LISA program on anchor blocks. Condition of the anchor block after receiving the appropriate tensile force from the round table at a span of 96 meters, the tensile force of the suspension bridge cable is 664.6 kN, resulting in a stress of 6.184 N/mm2 on the concrete surface of the anchor block using the concrete grade is fc 30 MPa, in the suspension cable of the bridge there is a tension of 22.26 N/mm2 at the point of work. The results of the analysis of the anchor block used on the Tuak River Suspension Bridge with a span of 96 m can meet the required criteria, namely the axial load-bearing capacity, which is greater than the maximum axial force that occurs in the Borpile configuration. In the analysis of the finite element method using the LISA FEA device, a significant stress occurs in the anchor block section with the suspension bridge cable as shown in Figure 9, this occurs because of the large tensile force on the suspension bridge cable and the ability of the anchor block to remain in a stable condition is known.